MOTIVASI PEMERINTAH INDONESIA MENERAPKAN KEBIJAKAN KERINGANAN PAJAK TERHADAP INVESTOR ASING YANG MASUK KE INDONESIA TAHUN 2015 - Anastasia Sarah Angela; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This present research describes the motivation of Indonesia Government to implementation of tax allowance policy for foreign investor that will invest in Indonesia in 2015. Global economic crisis and increase of United States economic has impact for economic of Indonesia. In 2014 Indonesia has defisit for trade and moneter transaction.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the motivation of Indonesia Government implementation of tax allowance policy for foreign investor that will invest in Indonesia. The theories applied in this research are merchantilism perspective with the decision making theory by Richad Snyder about internall and externall factors.The conclusion of the research that motivation of Indonesia Government to implementation of tax allowance policy are to keep economic and politic interest. This was due the defisit of moneter and trade payment, the weakness of Indonesian trades for foreign export, the weakness of trade balance and to support of foreign invesment to use rupiah in trade processing.Key words: motivation, implementations policy, tax allowance and investment